Peran dan Tantangan Koperasi dalam Pembangunan Ekonomi Masyarakat yang Bebas di Desa Namo Bintang Kecamatan Pancur Batu - Perkasa, Rypho Delzy; Sulistiani, Wiwid Nur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Cooperatives play a crucial role in the economic development of the community, especially in rural areas like Namo Bintang Village, Pancur Baru District. Cooperatives can be an effective means to stimulate economic growth and improve the welfare of the community. However, in carrying out their role, cooperatives face various challenges that need to be overcome in order to provide the greatest benefit to the community. This research aims to analyze the role of cooperatives in the economic development of the community in Namo Bintang Village and identify the challenges faced by cooperatives in achieving their goals. The research methodology used in this study is field research, which includes interviews and direct observations of cooperatives in Namo Bintang Village. The research identifies several challenges faced by cooperatives in Namo Bintang Village. First, the limited capital affects the ability of cooperatives to provide loans to their members. Second, the lack of access to a wider market limits the sale of cooperative products. Third, the lack of involvement of the younger generation in cooperative activities threatens the sustainability of cooperatives in the future. In addressing these challenges, several recommendations are given. First, the government needs to provide financial and technical support to cooperatives through mentoring and training programs. Second, cooperatives need to innovate in product marketing and expand their networks. Third, cooperatives must actively involve the younger generation by involving them in the decision-making process and providing opportunities for skills development.